Petanque pointing test: development and psychometric validation of a performance-based field instrument - Raihan Huzaky Arvajs; Nurul Ihsan; Muhammad Sazeli Rifki; Zulbahri Zulbahri (Indonesian Institute For Counseling, Education and Therapy, 2026)
The aim of this research was to design and validate the Petanque Test Pointing (PTP). The research design was a product development (R&D), the five-step ADDIE (namely: Analysis, Design, Development, Implementation, and Evaluation). For content validation, two expert petanque coaches and sport researchers in a related fields were chosen at random. Aiken's V was the content validity coefficient used. Aiken's V was determined as a content validity index of the instrument components and reliability was found by means of test-retest procedure i.e., repeated testing. Content validation across 12 components of PTP resulted in a mean Aiken's V of 0.908, which is above the commonly accepted cutoff point of 0.70 and it indicates an excellent degree of disagreement in the assessment of instrument items. The test-retest reliability was 0.712, which is considered high for an outdoor measure of performance. Conducting the PTP per player on the ground took 10 minutes approximately and no extra equipment was needed. Such characteristics indicate that PTP is a time-efficient and practical testing method, suitable for use among coaches. Therefore, the result is the development of Petanque Pointing Performance Test (PTP), a practical method of measuring pointing skills of petanque players, conducted by the players themselves, on the ground. PTP is validated and reliable as well as user-friendly in that it has been designed for usage in field. It can be used as a tool for an objective standard, a means of evaluation, and selection of petanque players with respect to their pointing skills. The findings present PTP as valid and reliable performance-based field measurement tool useful for assessment and development of petanque athletes pointing skills.